Influence of Nano-HA Coated Bone Collagen to Acrylic (Polymethylmethacrylate) Bone Cement on Mechanical Properties and Bioactivity - Li, Tao (PLoS One, 2015)
OBJECTIVE: This research investigated the mechanical properties and bioactivity of polymethylmethacrylate (PMMA) bone cement after addition of the nano-hydroxyapatite(HA) coated bone collagen (mineralized collagen, MC). MATERIALS & METHODS: The MC in different proportions were added to the PMMA bone cement to detect the compressive strength, compression modulus, coagulation properties and biosafety. The MC-PMMA was embedded into rabbits and co-cultured with MG 63 cells to exam bone tissue compatibility and gene expression of osteogenesis. RESULTS: 15.0%(wt) impregnated MC-PMMA significantly lowered compressive modulus while little affected compressive strength and solidification. MC-PMMA bone cement was biologically safe and indicated excellent bone tissue compatibility. The bone-cement interface crosslinking was significantly higher in MC-PMMA than control after 6 months implantation in the femur of rabbits. The genes of osteogenesis exhibited significantly higher expression level in MC-PMMA. CONCLUSIONS: MC-PMMA presented perfect mechanical properties, good biosafety and excellent biocompatibility with bone tissues, which has profoundly clinical values.